Potential Use of Alkaline-Activated Indonesian Pumice Powder as Lead Adsorbent in Solution System - Faridlotul Hasanah; Syaiful Anwar; Arief Hartono; Untung Sudadi (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2019)
Pumice is a volcanic material that found abundant in Indonesia. Owing to its physicochemical characteristics it can be utilized as a low-cost natural adsorbent for cationic contaminants. This study aimed to assess the performances of adsorbents prepared from NaOH-activated powder of Lombok and Kediri pumices for lead removal in solution systems based on their maximum adsorption capacity and removal efficiency parameters. The adsorption tests were done in batch experimentation using pumice powder of 74 μm particle size activated with 0.5, 1, and 2 M NaOH and lead solutions with initial concentrations of 0-260 mg.L-1. The most favorable NaOH activation concentration for both pumices was 0.5 M which resulted from Lombok pumice prepared-adsorbent with Pb maximum adsorption capacity based on linearized conventional and rearranged Langmuir isothermal adsorption models of 236.4 and 186.3 mg.g-1, while those of Kediri pumice were of 218.4 and 210.8 mg.g-1, respectively. The removal efficiency of both adsorbents were >80% at the initial Pb concentration of <100 mg.L-1 and around 50-80% at 100-260 mg.L-1. Both pumices are therefore considered potential to be utilized as an adsorbent for cationic contaminants in solution systems with reliable performances.